On the Emergence and Understanding of Asian Global Leadership - Chia, Audrey; Chong, Melody Pui Man; De Cremer, David; De Cremer, Hannah; De Pater, Irene E.; Eyring, Alison R.; Eyring, James D.; Gloor, Jamie L.; Kim, Sooyeol; Lim, Sandy; Liu, Lucy; Ma, Yu; et al. (De Gruyter, 2021)
In the twenty-first century, it is necessary for Asia to step up and assume a larger leadership role on the global stage, commensurate with its economic weight and interests. Eighty-eight percent of the increase in the numbers of the middle class in the next five years will take place in Asia, underscoring the reality that global business and leadership will be colored in significant ways by Asian values, approaches and strategies. This book explores how this may impact our view and conceptual approach to the notion of global leadership. The contributors to this collection explore and examine the concept of global Asian leadership and outcome implications at the societal, corporate and policy-making level. They argue that global leaders will increasingly focus on specific needs, values and strategies that are uniquely Asian, which emphasizes the reality that we most likely will have to redefine our notion of global leadership. This comprehensive study of the integration of Asian and global leadership will benefit those employed in the corporate, government and educational sectors as well as a broader audience with an interest in leadership, policy-making and economics.